11th International Congress on Targeted Anticancer Therapies. (September 2013) - Hélin, Valérie; Hammer, Ohad; Armand, Jean-Pierre
Paris, France, 4–6 March 2013 The Targeted Anticancer Therapies (TAT) conference provides a forum for in-depth discussion of emerging targeted agents for the treatment of cancer. TAT conferences are characterized by focus on emerging innovative agents with a cancer-specific molecular target, gathering the world's leading oncology Phase I investigators. They attract a mix of professionals with different backgrounds and roles in academia, industry and governmental agencies, all having a profound interest in the development of innovative cancer therapies. More than 500 delegates registered in 2013. Moreover, this year was organized, as part of the TAT congress, the first 'TAT biotech event'. New R&D initiatives often known as 'open innovation' are emerging to bring medicines to patients faster by facilitating public- and private-sector partnerships and collaborations, to solve common challenges encountered during the drug discovery and development process. We strongly believe that disruptive innovative anticancer therapies will come more and more from small biotechs, and that academic institutions have an active role to play in the field.